Analisis Segmentasi Wilayah Layanan ICONNET pada Jaringan MPLS (Multi-Protocol Label Switching) Berbasis VLAN (Virtual Local Area Network) terhadap Kepuasan Pelanggan di Wilayah Depok - Pipit Suryandani; Syah Alam; Yuli K. Ningsih; Lydia Sari; Indra Surjati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This document describes an analysis of ICONNET service area segmentation within a VLAN-Based MPLS (Multi-Protocol Label Switching) network and its impact on customer satisfaction in the Depok Region. Along with technological advancement, internet usage has become an essential need for both personal and business purposes. PLN ICON Plus, a subsidiary of PT PLN (Persero), develops its business through ICONNET products. However, full traffic on the backbone (BNG), which integrates ICONNET and corporate broadband networks, causes service degradation. To overcome this issue, VLAN-based regional segmentation and separate BNG implementations were introduced in each region. This innovation aims to distinguish backbone and corporate services, reduce congestion, and improve service quality. The analysis results are expected to contribute to network optimization and enhance customer satisfaction.